Pengaruh Faktor Minat, Motivasi Dan Lingkungan Masyarakat Terhadap Kesulitan Belajar Pada Mata Pelajaran Ekonomi Siswa Kelas X Di SMA Negeri 5 Padang - Dessyta Gumanti; Reni Respita; Wilgasia (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to analyze the influence of interest, motivation, and the social environment on students’ learning difficulties in Economics among Grade 10 students at SMAN 5 Padang, both partially and simultaneously. The study employed a descriptive quantitative approach. The population consisted of 412 Grade 10 students, with a sample of 80 students selected through proportional random sampling. Data were collected using a questionnaire and analyzed using multiple linear regression with SPSS version 26. Hypotheses were tested using the t-test for partial effects and the F-test for simultaneous effects. The results show that interest does not have a significant effect on learning difficulties (coefficient 0.377; t-value 0.995 < t-table 1.992), while motivation has a significant effect (coefficient 0.427) and the social environment also has a significant effect (coefficient 0.509) on learning difficulties. Simultaneously, interest, motivation, and the social environment influence students’ learning difficulties. These findings indicate that learning motivation and a supportive social environment play an important role in reducing learning difficulties, whereas interest does not show a significant partial effect.